234U(n,f) cross section with the FIC detector at CERN (n TOF) - Karadimos, D.; et al., ... (HNPS Advances in Nuclear Physics, 2020)
The analysis technique applied to the data and the reaction cross section 234U(n,f) from the FIC (Fission Ionization Chamber) detector at the n TOF facility is pre- sented here. A comparison of the measured neutron induced fission cross section of 234U nucleus is given with the available data from the bibliography. The measure- ments took place at the installation of CERN in Geneva. The detector was placed in front of the neutron beam for the determination of the neutron induced fission cross section of various isotopes of the Th cycle. For the data acquisition, several flash Analog to Digital Converter (fADC) channels were used. This facilitated the detailed off-line analysis of data since all information was stored in the computer. The automation of the process was required because the high amount of stored data. The data analysis aimed at the discrimination of fission events. For this end we had to deal with three main issues: i) The subtraction of the background, ii) the fitting of the pulses and iii) the automation of the process.